Surface characterization and methane activation on SnOx/Cu2O/Cu(111) inverse oxide/metal catalysts. Issue 32 (4th August 2021) - Kang, Jindong; Rui, Ning; Huang, Erwei; Tian, Yi; Mahapatra, Mausumi; Rosales, Rina; Orozco, Ivan; Shi, Rui; Senanayake, Sanjaya D.; Liu, Ping; Rodriguez, José A.
Abstract : Activating methane at low or medium temperatures, a pre-requisite for the conversion of this light alkane into high value chemicals, was achieved by a novel SnO x /Cu2 O/Cu(111) interface as evinced by STM, XPS, and DFT calculations. Abstract : To activate methane at low or medium temperatures is a difficult task and a pre-requisite for the conversion of this light alkane into high value chemicals. Herein, we report the preparation and characterizations of novel SnO x /Cu2 O/Cu(111) interfaces that enable low-temperature methane activation. Scanning tunneling microscopy identified small, well-dispersed SnO x nanoclusters on the Cu2 O/Cu(111) substrate with an average size of 8 Å, and such morphology was sustained up to 450 K in UHV annealing. Ambient pressure X-ray photoelectron spectroscopy showed that hydrocarbon species (CH x groups), the product of methane activation, were formed on SnO x /Cu2 O/Cu(111) at a temperature as low as 300 K. An essential role of the SnO x –Cu2 O interface was evinced by the SnO x coverage dependence. Systems with a small amount of tin oxide, 0.1–0.2 ML coverage, produced the highest concentration of adsorbed CH x groups. Calculations based on density functional theory showed a drastic reduction in the activation barrier for C–H bond cleavage when going from Cu2 O/Cu(111) to SnO x /Cu2 O/Cu(111). On the supported SnO x, the dissociation of methane was highly exothermic (Δ E ∼ −35 kcal mol −1 ) and the calculated barrier for activation (∼20 kcal mol −1 ) could be overcome at 300–500 K, target temperatures for the conversion of methane to high value chemicals.